Electoral turnout and income redistribution by the state: A cross-national analysis of the developed democracies - Vincent A. Mahler (Luxembourg Income Study (LIS), 2006)
This paper explores the sources of variation in state redistribution across 13 developed democracies over the 1979-2000 period, drawing upon data from the International Institute for Democracy and Electoral Assistance, the Luxembourg Income Study and the Comparative Study of Electoral Systems. The discussion begins with the median voter hypothesis, which predicts that the extent of state redistribution in a country will be positively related to the degree of pre-government inequality. In seeking to extend the median voter approach, the paper takes into account two additional variables, the level of electoral turnout and the degree to which turnout is skewed by income. The analysis confirms that pre-government inequality is indeed positively related to state redistribution. However, the predictive power of the median voter approach is significantly improved when account is taken of the level of electoral turnout and the extent to which the turnout rate reflects an income skew, variables which are themselves related. The link between turnout and redistribution is especially strong for social transfers, as opposed to taxes, and for the lower and middle, as opposed to the upper, part of the income spectrum.
Keywords: 330; Wahlverhalten; Verteilungspolitik; Politische Willensbildung; Vermögensverteilung; Neue politische Ökonomie; Schätzung; Welt